The global education movement : narratives of distinguished global scholars - Kirkwood-Tucker, Toni Fuss (Teaching and learning social studies., 2018)
"The pages of this book paint a portrait of thirteen scholars and their lifelong professional accomplishments in and contributions to teaching, service, and research in global international education around the world. Their extraordinary work contributed extensively to the development, direction and growth of the global education movement in the United States initiated by James M. Becker at Indiana University, USA, in the early 1960s. These scholars were honored with the Distinguished Global Scholar Award presented by the International Assembly of the National Council for the Social Studies, the largest professional journal for social studies educators in the United States. Their narratives comprise an intriguing mosaic of backgrounds, scholarship, and contexts from which their extraordinary work blossomed in building bridges--not walls--among peoples and nations. The publication is intended to honor the professional achievements in global international education of these scholars who have devoted their lives to creating a better world through their work. More importantly, this book exposes globally-minded individuals, educators, scholars, administrators, and policymakers around the world to empowering role models from Africa, Europe, and the United States and opportunity to learn about the multitude of professional activities, teachings, partnerships, exchange programs and research in which they might engage to promote a deeper understanding about the cultural, geographic, economic, social, and technological interconnectedness of the world and its people---the very purpose of global education"--